2016
DOI: 10.5005/jp-journals-10024-1868
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Dental Arch Changes and Buccal Bone Thickness in Patients treated with Self-ligating Brackets

Abstract: It should be noted that the bracket design does not influence the treatment course regarding transversal dimensions and buccal bone thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Medical equipment must be maintained in working order and periodically calibrated for effectiveness and accuracy of the results. [15][16][17][18][19] While purchasing medical equipment, the manufacturer company provides the service through annual maintenance contract (AMC) or comprehensive maintenance contract (CMC) by themselves or with the help of service providers. Planned preventive maintenance involves maintenance performed to extend the life of the equipment and prevent its failure and breakdown maintenance is performed to identify, isolate, and rectify a fault so that the out of order equipment, machine, or system can be restored to an operational condition.…”
Section: Discussionmentioning
confidence: 99%
“…Medical equipment must be maintained in working order and periodically calibrated for effectiveness and accuracy of the results. [15][16][17][18][19] While purchasing medical equipment, the manufacturer company provides the service through annual maintenance contract (AMC) or comprehensive maintenance contract (CMC) by themselves or with the help of service providers. Planned preventive maintenance involves maintenance performed to extend the life of the equipment and prevent its failure and breakdown maintenance is performed to identify, isolate, and rectify a fault so that the out of order equipment, machine, or system can be restored to an operational condition.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this study was to analyze the changes in periodontal health status and the effects on maxillary facial bone after the first year of orthodontic expansion using the Invisalign® clear aligner therapy. Although we found some studies that analyzed alveolar bone height and/or thickness, none of them correlated this information with clinical parameters 7,15 .…”
Section: Discussionmentioning
confidence: 86%
“…The different measurement methods, statistical evaluation, appliances and expansion amounts limit the comparison of the results of these two studies. Ibiapina et al 7 evaluated changes in transverse dimensions of upper arch and thickness of the buccal bone plate in patients undergoing orthodontic treatment with conventional and selfligating brackets, at CEJ+3mm and CEJ+6mm.The expansion was 1.57mm and 1.77mm for interfirst premolar, and 1.08 mm and 1.88mm for intersecond premolar. They observed that a small decrease of the buccal bone occurred similarly in both groups.…”
Section: A) Gingival Index (Gi) B) Plaque Index (Pi) C) Probing Pocke...mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have investigated the effect of both Damon and conventional bracket systems on the dimensions of the dental arch and the position of the incisors. Some studies showed that Damon system increased the arch length significantly compared to conventional bracket systems (7) while others believed that the total arch width is the same after orthodontic treatment irrespective of the type of the bracket system (8,9).…”
Section: Introductionmentioning
confidence: 99%